2001
DOI: 10.1021/ma001272p
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Scheme for Prediction of Deformation Mechanisms of Block Copolymers Based on Phase Behavior

Abstract: Block copolymers having different strengths of segregation are investigated with respect to their deformation behavior. Disordered block copolymers are deformed by the mechanism which corresponds to a glassy homopolymer. A crazing mechanism is observed for block copolymers with polystyrene as matrix. At the order−disorder transition (ODT), a change from crazing to cavitation mechanism is observed, confirming the change of deformation mechanism at the ODT. For intermediately and strongly segregated block copoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
(87 reference statements)
3
26
0
Order By: Relevance
“…Block copolymers contain two or more chains connected by covalent bonds that offer a means of combining the desirable characteristics of different polymers into a hybrid material 22 . The mechanical properties and swellability of the outer region of the MNs can be controlled by manipulating the overall average molecular weight of the polymer and the weight fraction of each block 20, 23 . In this study, we chose a polystyrene- block -poly(acrylic acid) (PS- b -PAA) block copolymer as the swellable material and PS homopolymer as a non-swellable material.…”
Section: Resultsmentioning
confidence: 99%
“…Block copolymers contain two or more chains connected by covalent bonds that offer a means of combining the desirable characteristics of different polymers into a hybrid material 22 . The mechanical properties and swellability of the outer region of the MNs can be controlled by manipulating the overall average molecular weight of the polymer and the weight fraction of each block 20, 23 . In this study, we chose a polystyrene- block -poly(acrylic acid) (PS- b -PAA) block copolymer as the swellable material and PS homopolymer as a non-swellable material.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our laboratory have demonstrated HVEM as a valuable tool for studying the micromechanical processes of deformation in heterogeneous polymers including block copolymers. [28][29][30][31] With the help of the HVEM we have investigated the deformation structures in cylindrical (LN1) and lamellar (ST2) samples. Representative HVEM micrographs are given in Figure 8.…”
Section: Micromechanical Deformation Behaviourmentioning
confidence: 99%
“…[28][29][30][31] This method even allows an in situ observation of deformation mechanisms in polymeric materials. Compared with the ultra-thin sections about 50-100 nm thick used for TEM investigations, deformation structures observed in semi-thin sections used in HVEM investigations (thickness in the order of ca.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 They found that disordered block copolymers ( N < 10.5) with a PS-rich composition had a similar deformation mechanism to that of polystyrene, whereas microphase-separated block copolymers showed improved tensile properties. The greatest improvement in terms of high strength and toughness was observed for intermediately segregated block copolymers (12.5 < N < 95).…”
Section: Introductionmentioning
confidence: 99%